Sebaceous carcinoma in a mature teratoma of the ovary - Renata Bernardini de Lima; Juliana Elizabeth Jung; Sérgio Ossamu Ioshii; Roger Mitsuo Kami (University of São Paulo, 2018)
The finding of a sebaceous carcinoma in a mature teratoma is rare in human pathology, with fewer than 10 cases currently reported in the literature. In this article, we report a case of sebaceous carcinoma in a mature teratoma of the ovary in a 59-year-old patient and discuss its histological findings.